2022
DOI: 10.5812/pedinfect-118889
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Groups/B2 Subgroup Distributions, Serogrouping and Identification of Virulence Factors in Extended-Spectrum Cephalosporin-Resistant Escherichia coli Strains Isolated from the Stool of Healthy Children Under 10 Years Old

Abstract: Background: Segregation of Escherichia coli (E. coli) into the phylogenetic groups was observed in the experiments so that group B2 contained the enteropathogenic E. coli (EPEC) strains and extraintestinal pathogenic E. coli (ExPEC). Objectives: This study aimed to identify B2 phylogenetic groups in the extended-spectrum Cephalosporins resistant E. coli isolated from the stool of healthy children under 10 years old. Methods: One hundred E. coli resistant to broad-spectrum Cephalosporins were collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Our study revealed that subgroup V was predominant, followed by subgroups VII, III, II, I, and VI. Similarly, another recent study reported that subgroup V had the highest frequency of the B2 subgroup isolated in ESBLproducing E. coli strains from healthy children stool samples (38). These results suggested there were a variety of B2 subgroups in host types and geographic regions.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…Our study revealed that subgroup V was predominant, followed by subgroups VII, III, II, I, and VI. Similarly, another recent study reported that subgroup V had the highest frequency of the B2 subgroup isolated in ESBLproducing E. coli strains from healthy children stool samples (38). These results suggested there were a variety of B2 subgroups in host types and geographic regions.…”
Section: Accepted Manuscriptmentioning
confidence: 76%